An Overview of the Quality of Life of Former Narcotics Addicts at the East Java BNNP Primary Rehabilitation Clinic: Gambaran Kualitas Hidup Mantan Pecandu Narkotika di Klinik Rehabilitasi Pratama BNNP Jatim - Moch Ainul Yaqin; Riza Noviana Khairunnisa (Universitas Negeri Surabaya, 2023)
This study aims to describe the quality of life of ex-narcotics addicts when they are rehabilitated and to find out what factors affect the quality of life. The method used in this research is qualitative with a case study approach. Data analysis using thematic analysis. The results of this study revealed that both subjects before being rehabilitated had poor physical, psychological, social and environmental conditions. Meanwhile, when the two subjects were rehabilitated, they had improvements in terms of physical, psychological, social relations and environmental dimensions. Then the factors that influence the quality of life are age, education, marital status. researchers interpret the quality of life as a process of individual life to be better.